VARIASI ARAH AKSIAL TERHADAP SIFAT FISIKA DAN MEKANIKA KAYU MINDI(Melia azedarach Linn.) DARI DESA SENANGGALIH KABUPATEN LOMBOK TIMUR - Putri; Wulandari, Febriana Tri; Lestari, Andi Tri (JURNAL RIMBA LESTARI, 2023)
The demand for commercial timber in Indonesia continues to rise, while the availability of forest resources is steadily declining, both in terms of production forest area and wood quality. Many native wood species remain underutilized in the Indonesian wood industry due to limited information regarding their properties. One such species, Mindi wood (Melia azedarach Linn.), has been used by local communities but is not widely recognized as a commercial timber alternative. Mindi wood holds potential as a substitute for high-quality commercial timber; however, research on its physical and mechanical properties remains scarce. This study aims to evaluate the axial variation in the physical and mechanical properties of Mindi wood from Senanggalih Village, East Lombok Regency, and to assess the influence of axial position on these properties. The study employed a non-factorial Completely Randomized Design (CRD) with three axial sections (base, middle, and top) as treatments, each replicated three times. Results indicated that axial position significantly affected certain physical properties, including kiln-dry specific gravity, radial shrinkage (from fresh to kiln-dry), and longitudinal swelling (from air-dry to wet). However, no significant effect was observed on moisture content (fresh air or air-dry), fresh specific gravity, air-dry density, or shrinkage and swelling in the tangential, radial, and longitudinal directions for various moisture conditions. In terms of mechanical properties, no significant effect of axial position was found on Modulus of Elasticity (MoE) and Modulus of Rupture (MoR). These findings suggest that Mindi wood is suitable for light construction applications such as furniture manufacturing, as well as for composite wood products including plywood, particleboard, and fiberboard.